Improved group-specific primers based on the full SILVA 16S rRNA gene reference database - Lojan, P. (2017)
Quantitative PCR (qPCR) and community fingerprinting methods, such as the Terminal Restriction Fragment Length Polymorphism (T-RFLP) analysis, are well-suited techniques for the examination of microbial community structures. The use of phylum- and class-specific primers can provide enhanced sensitivity and phylogenetic resolution as compared with domain-specific primers. To date, several phylum- and class-specific primers targeting the 16S ribosomal RNA gene have been published. However, many of these primers exhibit low discriminatory power against non-target bacteria in PCR. In this study, we evaluated the precision of certain published primers in silico and via specific PCR. We designed new qPCR and T-RFLP primer pairs (for the classes Alphaproteobacteria and Betaproteobacteria, and the phyla Bacteroidetes, Firmicutes and Actinobacteria) by combining the sequence information from a public dataset (SILVA SSU Ref 102 NR) with manual primer design. We evaluated the primer pairs via PCR using isolates of the above-mentioned groups and via screening of clone libraries from environmental soil samples and human faecal samples. As observed through theoretical and practical evaluation, the primers developed in this study showed a higher level of precision than previously published primers, thus allowing a deeper insight into microbial community dynamics.